Upaya Pencegahan Anemia pada Remaja Putri melalui Penggunaan Video Animasi - Yulia Sari; Mina Yumei Santi; Niken Purbowati; Shentya Fitriana (Jurnal Bidan Cerdas, 2022)
Introduction: Anemia causes decreased endurance, fatigue, weakness, lethargy, negligence, impaired concentration in learning and worsening academic achievement. The lack of knowledge of young women has an impact on negative attitudes towards efforts to prevent anemia. Purpose: To determine the effect of balanced nutrition animated videos on efforts to prevent anemia in young women. Purpose: To determine the effect of balanced nutrition animated videos on efforts to prevent anemia in young women. Methods: Quantitative research using a quasi-experimental design with a pretest-posttest approach with a control group design. A sample of 50 female adolescents in each group was determined using a proportional random sampling technique, then the knowledge and attitude scores of adolescents were measured before and after treatment. Data analysis used the independent t test. Results: The average score of female adolescents' knowledge about efforts to prevent anemia in the treatment group that was given the intervention was higher than the control group (p=0.0001). The average score of the attitudes of young women regarding efforts to prevent anemia in the treatment group was higher than that of the control group (p=0.0001). Conclusion: Animated video on balanced nutrition can be used as an extension medium in providing education to students, especially young women, in preventing anemia.